2009
DOI: 10.1143/apex.2.096001
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Plasma Etching Process

Abstract: Combinatorial plasma etching, which can be used to acquire large databases and to establish process-science map, is proposed for developing a process for etching low-k dielectric films. This process promises to save the cost and time spent on accumulating scientific databases for optimizing etching processes since it can acquire many results in a single operation. We interpreted the etching characteristics by using internal parameters such as the ion and the radical densities. By doing this, it is possible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Ammonia molecules are also created in the N 2 and H 2 plasma. [18,[88][89][90][91][92][93][94][95][96] Only a few studies of the N 2 /H 2 PEMOCVD were reported. [30,32,35,37,40] It is also found that a small amount of ammonia species of %0.22 vol% was generated in the REMOCVD system, [16] suggesting that NH x radicals may be generated in the chamber.…”
Section: Oesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonia molecules are also created in the N 2 and H 2 plasma. [18,[88][89][90][91][92][93][94][95][96] Only a few studies of the N 2 /H 2 PEMOCVD were reported. [30,32,35,37,40] It is also found that a small amount of ammonia species of %0.22 vol% was generated in the REMOCVD system, [16] suggesting that NH x radicals may be generated in the chamber.…”
Section: Oesmentioning
confidence: 99%
“…[16] There are also data that NH 3 gas is generated from N* and H* as described in refs. [18,[88][89][90][91][92][93][94][95][96].…”
Section: N 2 /H 2 Gas Ratiomentioning
confidence: 99%
“…Fourth, and last but not least, the combinatorial plasma process, which is an experimental system with a facility dedicated to this purpose, has a high capability to supply large databases; it was initially proposed for database acquisition for parameter maps, but it can be ready for that for machine learning. Moon et al 92) and Setsuhara et al 93) proposed the concept of a combinatorial plasma etching process and verified its validity using experimental results. The initial concept of combinatorial approaches to chemistry was proposed and verified in general cases in which continuous parameter variation in multi-dimensions is possible to obtain experimental samples as corresponding outputs.…”
Section: Methods Suggested In Internet-of-things Technologymentioning
confidence: 94%
“…[5][6][7] In this process, the N atom is known to form a protective layer on the sidewall of the patterns against the etching species of the H atom. [14][15][16][17][18][19] Nagai et al reported that the etching profile of 65-nm line and space (L&S) mask-patterned low-k organics with H 2 /N 2 plasma was affected by approximately 10 percent of variation in the radical density ratio. 14) It has been a great concern for the precise control of plasma etching to consider that the condition of the reactor wall surface affects the plasma chemistry in the reactor.…”
mentioning
confidence: 99%
“…In fact Moon et al indicated that the surface loss probabilities for H and N atoms ranged between 0.03 and 0.16, depending on the wall materials and gas mixture ratio. 18,19) This loss probability will affect the densities in the range of 5 factors at maximum.…”
mentioning
confidence: 99%